Visualization of the research landscape on the 20 m shuttle run test in the last 15 years: bibliometric analysis with VOSviewer of the most cited studies - Becerra-Patiño, Boryi A.; Paucar Uribe, Juan David; Yáñez-Sepúlveda, Rodrigo; Reyes-Amigo, Tomas; Mello, Júlio Brugnara; Martins, João; Gaya, Anelise Reis; López-Gil, José Francisco; Olivares-Arancibia, Jorge (Frontiers in Sports and Active Living, 2025)
IntroductionVarious studies have applied the 20-meter shuttle run test (20mSRT) to estimate cardiorespiratory fitness in different population groups, with the aim of associating test performance with the physiological, psychosocial, and cognitive health of children and young people. However, to date, no bibliometric review that analyzes the research landscape has been conducted. The objective was to conduct a bibliometric review to develop an overview of the current state of scientific literature and identify research trends in the study of the 20mSRT in the Web of Science and PubMed databases.MethodsThe final sample consisted of 797 documents. For the publication period, between 2010 and 2021, there was a considerable increase of 248.1% of the number of investigations. The year 2011 had the highest citation count, and the trend reveals low citation rates for the years 2018 and 2023, with decreases of −70.40% and −86.65% compared with the years 2012 and 2019, respectively.ResultsMost of the production is in research articles (95.98%). The most cited authors are Ruiz, Castro-Piñero, Mayorga-Vega, Ortega, and Tomkinson. The five concepts with the highest occurrence in the research are children (n = 290), cardiorespiratory fitness (n = 205), adolescents (n = 203), performance (n = 164), and aerobic fitness (n = 146). The journals with the most published documents are the Journal of Strength and Conditioning Research (n = 45), the International Journal of Environmental Research and Public Health (n = 42), and the Journal of Sports Sciences (n = 25). The countries with the highest number of published documents and citations are Spain (n = 187 documents and 6,209 citations), the United States (n = 112 documents and 3,475 citations), Australia (n = 85 documents and 2,393 citations), and Sweden (n = 54 documents and 4,121 citations).DiscussionAn analysis of the existing knowledge produced by the 20mSRT revealed that there is a preference for studying the school-age stage, with cardiorespiratory fitness variables associated with physical activity and sedentary time. Finally, there are different applications of the 20mSRT in various population groups, ranging from the evaluation of cardiorespiratory fitness in children, adolescents, and adults, as well as in specific groups of athletes.